Cover Feature: The Chemistry and Kinetics of Polyethylene Pyrolysis: A Process to Produce Fuels and Chemicals (ChemSusChem 7/2020). Issue 7 (6th April 2020) - Zhao, Dongting; Wang, Xianhua; Miller, James B.; Huber, George W.
Abstract : The Cover Feature, designed by Xin Zou and Dongting Zhao, shows that pyrolysis can convert polyethylene plastic wastes into paraffins, olefins, dienes, and aromatics, which are recycled and find their end application, such as transportation fuels, via further refining processes. More information can be found in the Full Paper by D. Zhao et al. on page 1764 in Issue 7, 2020 (DOI: 10.1002/cssc.201903434 ).